Coprecipitation technique to prepare BaNb2O6 - Natarajan, N; Samuel, V; Pasricha, R; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
A mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and niobium ions as barium oxalate and niobium hydroxide under basic conditions. This precursor on calcination at 750degreesC yielded BaNb2O6 ceramics. This is a much lower temperature as compared to that prepared by traditional solid-state method (1000degreesC), as reported for the formation of BaNb2O6. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ammonia; Ceramics; Electron microscopy; niobium oxide; Oxides

Direct synthesis of secondary amines from alcohols and ammonia catalyzed by a ruthenium pincer complex - Balaraman, Ekambaram; Srimani, Dipankar; Diskin-Posner, Yael; Milstein, David (Catalysis Letters, 2015)
Efficient and selective direct synthesis of secondary amines from primary alcohols and ammonia with liberation of water has been achieved, with high turnover numbers and with no generation of waste. In case of benzylic alcohols, imines rather than amines are obtained. This atom economical, environmentally benign reaction is homogenously catalyzed by a well-defined bipyridine based Ru(II)-PNN pincer complex.
Keywords: Alcohol; Ammonia; Homogenous catalysis; Ru-pincer complex; Secondary amine